Efektivitas Model Pembelajaran Inquiry terhadap Hasil Belajar IPS - Sherly Harefa; Isbandiyah I; Andriana Sofiarini (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2020)
This study aims to determine the effectiveness of the Inquiry learning model on social studies learning outcomes of Grade VII students at SMP Negeri 13 Lubuklinggau. The research method used is a quantitative research method using a quasi-experimental approach. The population is all students of class VII in 2018/2019 consisting of 3 classes totaling 79 and as a sample are class VII 1, amounting to 25 students. The data collection technique used was a multiple choice test technique of 28. problem. Based on the t-test analysis, it was concluded that the Inqury learning model was effective against social studies learning outcomes.